2022
DOI: 10.3389/fcell.2022.731831
|View full text |Cite
|
Sign up to set email alerts
|

Naringin Mediates Adult Hippocampal Neurogenesis for Antidepression via Activating CREB Signaling

Abstract: The brain-derived neurotrophic factor/tropomyosin receptor kinase B/cAMP response element-binding protein (BDNF/TrkB/CREB) signaling pathway is a critical therapeutic target for inducing adult hippocampal neurogenesis and antidepressant therapy. In this study, we tested the hypothesis that naringin, a natural medicinal compound, could promote adult hippocampal neurogenesis and improve depression-like behaviors via regulating the BDNF/TrkB/CREB signaling pathway. We first investigated the effects of naringin on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 69 publications
1
14
0
Order By: Relevance
“…19 On the contrary, several studies have pointed out the promising antidepressant and anxiolytic properties of naringin. 10,11 Treatment low-and high-dose naringin restored the level of T4 and significantly boosted the TSH level, which corroborated with the work of Panda and Kar. 20 Inhibition of thyroid peroxidase and deiodinase enzymes by naringin explained their results.…”
Section: ■ Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…19 On the contrary, several studies have pointed out the promising antidepressant and anxiolytic properties of naringin. 10,11 Treatment low-and high-dose naringin restored the level of T4 and significantly boosted the TSH level, which corroborated with the work of Panda and Kar. 20 Inhibition of thyroid peroxidase and deiodinase enzymes by naringin explained their results.…”
Section: ■ Discussionsupporting
confidence: 82%
“…Naringin (4′,5,7-trihydrocyflavanone-7- O -rhamnoglucoside) is a natural bioflavonoid found in many fruits including citrus fruits, and it gives them their bitter taste and sour flavor. Naringin has been reported to possess a broad spectrum of pharmacological properties including anti-inflammatory, antioxidative, and antiapoptotic properties, as well as advantageous neuroprotective effects and memory-enhancing properties. , Furthermore, it showed promising results in treating many diseases including Alzheimer’s, metabolic syndrome, and diabetes . Additionally, previous studies have pointed to the neuroactivity of naringin, which demonstrated beneficial neurobehavioral effects including anxiolytic, antidepressant, and memory-enhancing properties through modulation of 5-HT content and alleviation of oxidative stress in the hippocampus region. , Recently, the modulation of Wnt/β-catenin signaling has been reported to be involved in the therapeutic effects of naringin in different disorders. , However, the potential protective effects of naringin against the psychological changes induced by hyperthyroidism have not been investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the prophylactic effect of amphotericin B liposome on chronic stress-induced behavioral abnormalities in mice could also be mediated by its preventive effect on the disrupted CREB-BDNF signaling pathway in the brain. Because CSDS exposure and disruption of CREB-BDNF signaling are closely related to the impairment of neurogenesis in the brain (Maitra et al, 2020;Jiang et al, 2021;Gao et al, 2022) and stimulation of the innate immune system can promote neurogenesis (Reshef et al, 2017;Al-Onaizi et al, 2020;Seong et al, 2022), the prophylactic effect of amphotericin B liposomes on chronic stress-induced behavioral abnormalities might also be mediated by enhancing neurogenesis through improving CREB-BDNF signaling function. These uncertainties should be explored in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Data from experimental models have shown that naringin modulates key biological pathways related to cellular stress response, mitochondrial function, and metabolism (Biala et al, 2010; de Oliveira et al, 2017; Li et al, 2016; Liu et al, 2014; Petry et al, 2021; Syed et al, 2020). Particularly in the context of neurodegenerative diseases, naringin has been shown to increase neurogenesis and improve antioxidant defenses, ATP production, and the turnover of damaged mitochondria by regulating mitochondrial dynamics and biogenesis through sirtuins (SIRT), adenosine monophosphate‐activated protein kinase (AMPK), and the serine/threonine kinase (AKT) pathway activation (Gao et al, 2022; Okuyama et al, 2018; Wang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%